Guidelines for the ecolabelling of fish and fishery products from marine capture fisheries = (Food and Agriculture Organization of the United Nations, 2005)
The guidelines are of a voluntary nature. They are applicable to ecolabelling schemes that are designed to certify and promote labels for products from well-managed marine capture fisheries and focus on issues related to the sustainable use of fisheries resources. The guidelines refer to principles, general considerations, terms and definitions, minimum substantive requirements and criteria, and procedural and institutional aspects of ecolabelling of fish and fishery products from marine capture fisheries.